Gambaran Pengetahuan, Sikap, dan Minat Masyarakat Terhadap Konsumsi Jamu sebagai Produk Tumbuhan Obat dalam Kemasan Modern - puji ningrum, Sekti (BENZENA Pharmaceutical Scientific Journal, 2025)
Jamu is a traditional medicinal product made from medicinal plants that has long been used by Indonesians to maintain health. Modern lifestyles have encouraged innovation in modern, more practical and attractive packaging, thus influencing public acceptance of these products, which is influenced by knowledge, attitudes, and interests. This study aims to determine the public's knowledge, attitudes, and interests regarding the consumption of jamu, a medicinal plant product, in modern packaging. This study used a descriptive method with a quantitative approach. Data collection was conducted through a questionnaire administered to respondents who met the research criteria. The data obtained were analyzed descriptively to describe the public's level of knowledge, attitudes, and interests. The results indicate that public knowledge regarding jamu is in the good category. Public attitudes toward jamu in modern packaging tend to be positive, and public interest in consuming jamu in modern packaging is quite good. These findings indicate that the public has a fairly good understanding and acceptance of jamu as a medicinal plant product developed in modern packaging.Keywords: Jamu, Consumption, Knowledge, Attitudes, Interests